Microbiome Structure and Function in Woodchip Bioreactors for Nitrate Removal in Agricultural Drainage Water - Jéglot, Arnaud; Audet, Joachim; Sørensen, Sebastian Reinhold; Schnorr, Kirk; Plauborg, Finn; Elsgaard, Lars (Frontiers in Microbiology, 2021)
Woodchip bioreactors are increasingly used to remove nitrate (NO3-) from agricultural drainage water in order to protect aquatic ecosystems from excess nitrogen. Nitrate removal in woodchip bioreactors is based on microbial processes, but the microbiomes and their role in bioreactor efficiency are generally poorly characterized. Using metagenomic analyses, we characterized the microbiomes from three full-scale bioreactors in Denmark, which had been operating for more than four years. The microbiomes were dominated by Proteobacteria and especially the genus Pseudomonas, which is consistent with heterotrophic denitrification as the main pathway of NO3- reduction. This was supported by functional gene analyses, showing presence of the full suite of denitrification genes from NO3- reductases to nitrous oxide reductases. Genes encoding for dissimilatory NO3- reduction to ammonium were found only in minor proportions. In addition to NO3- reducers, the bioreactors harbored distinct functional groups, such as lignocellulose degrading fungi and bacteria, dissimilatory sulfate reducers and methanogens. Further, all bioreactors harbored genera of heterotrophic iron reducers and anaerobic iron oxidizers (Acidovorax) indicating a potential for iron-mediated denitrification. Ecological indices of species diversity showed high similarity among and within the bioreactors, indicating that the woodchip resource niche was important in shaping the microbiome. This trait may be exploited in the development of common microbiological strategies to increase the NO3- removal from agricultural drainage water.